The function of VEGF-A in lens development: Formation of the hyaloid capillary network and protection against transient nuclear cataracts - Garcia, Claudia M. (2008)
A network of capillaries branches from the hyaloid vascular system and surrounds the mammalian lens throughout much of its embryonic development. These vessels are presumed to be important for the growth and maturation of the lens, although the lenses of non-mammalian vertebrates have no comparable vessels. Over expression of VEGF-A in the lens increases the extent of these capillaries, but it is not known whether VEGF-A from the lens is necessary for their formation or survival. To address this question, we deleted Vegfa in the lens. This prevented the formation of the capillary networks adjacent to the lens capsule, but did not alter nearby hyaloid vessels at the surface of the retina. Postnatal lenses lacking Vegfa were smaller than wild type and, by 1 month of age, many had mild nuclear opacities. These opacities regressed with age. The lens is hypoxic throughout most of life and VEGF-A expression is often regulated by the transcription factor, hypoxia inducible factor-1. Lenses lacking Hif1a were of apparently normal size, had markedly reduced levels of mRNA for VEGF-A and glyceraldehyde-3-phosphate dehydrogenase, but had normal-appearing capillaries covering their surface. We conclude that VEGF-A from the lens is necessary for the formation of the normal hyaloid vascular system and that lack of these capillaries was the most likely cause of growth retardation during fetal and early postnatal lens development. In the absence of HIF-1 function, sufficient VEGF-A is produced by the lens to promote capillary formation. Further study is needed to explain the formation of the mild opacities seen in some lenses lacking Vegfa and their regression later in life.